mcr-4 carrying Escherichia coli isolates of Europe exhibit a high genetic diversity but a highly conserved plasmid type encoding the colistin resistance - García-Meniño, Isidro (2021)
Background: Colistin represents an important antimicrobial for the veterinary and human sector. Besides its outstanding antimicrobial use in gastrointestinal infections in animals, it is currently a last-line treatment option for human infections caused by multidrug-resistant Gram-negative bacteria. Successively after the description of the first mobile colistin resistance (mcr-1) element in Escherichia coli, the identification of other genes (mcr-2 to mcr-10) and variants has forced the understanding of the colistin resistance and dissemination mechanisms in Enterobacterales. Material and Methods For comparative analysis, a collection of Spanish (n=28), German (n=14) and Portuguese (n=9) E. coli isolates of porcine origin exhibiting the mobile colistin resistance determinant mcr-4, were subjected to phenotypic and genotypic in depth characterization. The isolates were investigated for their antimicrobial susceptibility, macrorestriction profiles (XbaI-PFGE), plasmid patterns (S1-PFGE) and plasmid transmission (in vitro filter mating studies). Short-read whole-genome sequencing (WGS) data were used for in silico-based typing of the genomes. Results: Overall, the investigated isolates of the three countries differed substantially in their macrorestriction profiles. While Portuguese and Spanish isolates exhibited a closer phylogenetic identity, in relation with their geographic origin, German isolates showed high heterogeneity. Similar results were observed from S1-PFGE analysis. However all isolates showed a low size mcr-4 carrying plasmid (range10 to 25 kb). In vitro transmission to the sodium azide-resistant E. coli J53 strain was confirmed in at least 50% of the Spanish and Portuguese isolates. Interestingly, most of the transconjugants harbored two plasmids of which only one carried the mobilizable mcr-4 plasmid, while the second would probably act as a helper for the transmission. While the mcr-4 plasmids seem to be based on a highly conserved ColE10 plasmid backbone, the majority of their host are highly heterogeneous. Conclusions: Our results indicate a close relationship of the individual mcr-4 carrying plasmids of Portugal, Spain and Germany. Thus, we suppose that dissemination of the conserved plasmid-type is based on a common ancestor However, the impact of this gene is currently unknown, since no comprehensive information on mcr determinants in colistin-resistant isolates from human infections exists.